2014
DOI: 10.4300/jgme-d-13-00396
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Physical Activity in Minnesota Internal Medicine Resident Physicians

Abstract: Background Regular physical activity plays an important role in the amelioration of several mental health disorders; however, its relationship with burnout has not yet been clarified. Objective To determine the association between achievement of national physical activity guidelines and burnout in internal medicine resident physicians. Methods A Web-based sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 33 publications
10
55
0
Order By: Relevance
“…There was no significant relationship between number of children's of residents and burnout in this study. Which is consistent with the results of Park et al and Olson et al studies (Park at al, 2016;Olson et al, 2014). Also Martini et al (2004) reported that 56.4% of residents without children met the criteria for burnout while it was found in 36.4% of residents with one or more child, (indicating no significant difference).…”
supporting
confidence: 90%
“…There was no significant relationship between number of children's of residents and burnout in this study. Which is consistent with the results of Park et al and Olson et al studies (Park at al, 2016;Olson et al, 2014). Also Martini et al (2004) reported that 56.4% of residents without children met the criteria for burnout while it was found in 36.4% of residents with one or more child, (indicating no significant difference).…”
supporting
confidence: 90%
“…These findings are similar to a recent study of internal medicine residents that found that residents able to meet physical activity guidelines were less likely to be burned out. 24 Whether this relates to the positive effect of physical activity or the ability of residents to take time in their schedules to exercise is less certain; those who are able to make time for physical activity are presumably working less or have fewer outside demands on their time.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies have shown that the recommended amount of exercise has been associated with improved QOL and learning, higher resiliency, and lower burnout. [22][23][24] Other research has demonstrated that resident and fellow physicians are less likely to engage in physical activity compared to medical students and staff physicians, with a higher body mass index associated with more work hours per week. 25 The same study also found that residents who worked less than 70 hours a week and had no children were more likely to meet the CDC guidelines for exercise.…”
Section: Discussionmentioning
confidence: 99%